Directly replanting with GF296 extends the years of ratooning and yield in sugarcane - Huiwen Zhou; Hanmin Luo; Youchen Wei; Hongchui Wei; Yuanke Wei; Ming Liu; Ming Li; Jianhua You; Yangrui Li; Haifeng Yan; Lihang Qiu (Scientific Reports)
Abstract Sugarcane (Saccharum officinarum L.) is a sugar crop capable of ratoon cultivation, and its ratooning ability directly relates to sugarcane production costs and planting benefits. Sugarcane ridges with missing seedlings and gaps are an important reason for the reduction in the number of effective stalks and the years of ratooning of ratoon sugarcane. Therefore, analyzing the differences and correlations in important agronomic traits during yield formation within ratoon sugarcane populations after replanting treatment is of paramount importance for guiding ratoon cultivation. In this study, the 3rd-year ratoon sugarcane of the main varieties Guiliu 2 (GL2), Guitang 44 (GT44), and Yuetang 00236 (YT236), which are widely cultivated, served as the target population for replenishment. Using stem cuttings of Guifu 98-296 (GF296) as the replanting material, replanting treatment was applied to sugarcane ridges with missing seedlings and gaps in the planting plots of the after mentioned three varieties. Unreplanted populations served as their respective controls (CK). At harvest in the 3rd, 4th, and 5th ratoon years, data on important agronomic traits and sucrose content of the sugarcane populations under the replanting and non-replanting treatments were investigated. An analysis was conducted to ascertain the differences and correlations among agronomic trait indicators. The economic benefits of the replanting treatment and CK were calculated. The findings of the study demonstrated that the number of effective stalks in the replanted populations of GL2, GT44, and YT236 was significantly higher than in the non-replanted control groups (CK), with an increase ranging from 10.72 to 45.26%. The yield of both the replanted and CK groups for GL2, GT44, and YT236 decreased by 9.56–54.14% with prolonged the years of ratooning. Conversely, the yield of the replanted populations increased by 28.19–158.61% over extended ratooning years. Significant variations were observed in plant height, stem diameter, and single-stalk weight among the original ratoon sugarcane varieties (GL2, GT44, YT236) and their respective CK groups across different ratooning years. In the non-replanted groups, the number of effective stalks exhibited a highly significant negative correlation with the years of ratooning (correlation coefficients: GL2: − 0.907, GT44: − 0.931, YT236: − 0.756), and yield also showed a highly significant negative correlation with the years of ratooning (GL2: − 0.915, GT44: − 0.905, YT236: − 0.930). Notably, after replanting, the negative correlation between the years of ratooning and both yield and effective stalk number was eliminated, indicating improved population structure. Furthermore, the replanted GL2, GT44, and YT236 populations exhibited increased economic benefits, with cumulative net income gains over three ratooning seasons of 48,120.80 CNY ha−1, 46,765.80 CNY ha−1, and 42,398.60 CNY ha−1, respectively. In conclusion, GF296 replanting effectively extended the years of ratooning by three years, substantially enhanced economic returns, and is suitable for large-scale implementation. The present study provides a theoretical basis for constructing high-yield populations, maximising ratoon potential, and achieving high-efficiency cultivation.